The Effect of Adding Coconut Coir Fiber on Compressive Strength, Tensile Strength, and Concrete Flexural Strength in Eco-Friendly Tetrapod Planning in Coastal Areas of IKN Supporting Cities - Hijriah, Hijriah; Muhding, Noor Zaqiyah; Wahab, Muhammad Fajrin; Fauzi, Ardiansyah; Yanti, Rossana Margaret Kadar; Sukmara, Riyan Benny (Universitas Negeri Padang, 2024)
Beaches often experience erosion or abrasion problems caused by various factors, such as climate change which triggers rising sea levels, high waves, human activities such as beach reclamation, and infrastructure construction that is not environmentally friendly, triggering erosion on the coast. In the coastal area of the city that supports IKN, which is located in the Balikpapan area, Manggar Beach, also experiences abrasion which causes land to narrow in that area. The abrasion that occurs erodes the coastal area around 7-8 meters every year. To produce environmentally friendly infrastructure, this research carried out the addition of coconut fiber waste components to tetrapod concrete used for breakwater construction. In this research, variations in the addition of coir used were 0%, 1%, 2%, 3%, 4% and 5%. The aim was to find out how much influence the addition of coconut coir waste to the concrete mixture had on the compressive strength, tensile strength and flexural strength of the concrete in tetrapods. and produce concrete that uses coconut fiber waste as an alternative material for tetrapod concrete as breakwater armor. Based on the analysis results, the quality of the concrete was 23 Mpa. This value was determined based on wave generation analysis. In addition, it is known that variations in coconut fiber affect the slump, compressive strength, flexural and split tensile test values of concrete. Based on the slump test results, it was found that the greater the variation of coconut fiber in the concrete, the lower the resulting slump test value. In testing the compressive, flexural and split tensile strength, it was found that the optimal composition for adding coconut fiber was 3%, in this composition the amount of coconut fiber fiber was able to improve the mechanical properties of tetrapod concrete compared to other compositions.